Modal characteristics and damping enhancement of carbon fiber composite auxetic double-arrow corrugated sandwich panels. (1st November 2018) - Ma, Li; Chen, Yun-Long; Yang, Jin-Shui; Wang, Xin-Tao; Ma, Guo-Lin; Schmidt, Rüdiger; Schröder, Kai-Uwe
Abstract: Auxetic materials and structures as a class of metamaterials have been extensively studied and evaluated for many applications. This paper focuses on the fabrication and vibration damping of the carbon fiber composite auxetic double-arrow corrugated sandwich panels (DACSPs). The negative Poisson's ratio effects of the composite auxetic DACSPs are analytically studied based on energy method. 3D finite element (FE) models combined with Modal Strain Energy (MSE) approach are developed to investigate their vibration and damping characteristics. To validate the numerical models in the present study, the composite auxetic DACSPs and such structures inserted with high damping layer are designed and manufactured. Modal vibration and three-point bending tests are conducted to investigate their vibration damping and bending responses. The results show that the 3D FE models combined with MSE approach are valid to predict the modal properties of the composite auxetic DACSPs. The influence of the different inclined corrugated angles on the natural frequencies and damping loss factors are plotted and discussed. Meanwhile, the effect of Poisson's ratio on the nominal Young's modulus, natural frequencies and damping loss factors of the composite auxetic DACSPs are also revealed. It is observed from the results that it is possible to obtain both increased stiffness and high damping capacity of such composite auxetic DACSPs by optimizing the inclined corrugated angles and inserting suitable damping layers.